2014
DOI: 10.1007/s00330-014-3162-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal tissue elasticity by acoustic radiation force impulse quantification with histopathological correlation: preliminary experience in chronic kidney disease

Abstract: • Acoustic radiation force impulse (ARFI) can quantify tissue elasticity of CKD kidney. • Despite standardized measurement, ARFI-estimated elasticity did not correlate with renal fibrosis. • Effects of pathological complexity and tissue perfusion on renal stiffness warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 25 publications
2
92
2
1
Order By: Relevance
“…Other studies published so far, comparing histological results with elastography in native kidneys, did not reach similar conclusions: Wang et al found no correlation of kidney SWV with: interstitial fibrosis, tubular atrophy, glomerulosclerosis index [9], while Cui et al found that renal fibrosis is associated with an increase of SWV [22].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Other studies published so far, comparing histological results with elastography in native kidneys, did not reach similar conclusions: Wang et al found no correlation of kidney SWV with: interstitial fibrosis, tubular atrophy, glomerulosclerosis index [9], while Cui et al found that renal fibrosis is associated with an increase of SWV [22].…”
Section: Discussionmentioning
confidence: 87%
“…Despite the fact that elastography is an accurate approach to liver fibrosis grading, data published so far regarding the influence of specific histological changes on the renal stiffness is quite scarce [9]. The aim of the present study is to assess the relationship between kidney SWV and chronic histological changes (glomerulosclerosis, interstitial fibrosis, arteriolo-hyalinosis) in patients diagnosed with chronic glomerulonephritis (CGN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Aixplorer system is good for kidney applications by using real-time and continuous color mapping, when the continuous motion due to arterial pulsation and respiration and the small size of the kidney are considered. Even though there are no data comparing the Aixplorer system to systems from other vendors in terms of kidney elastography, acoustic radiation force impulse imaging with the Acuson S2000 system (Siemens AG, Erlangen, Germany) has also been used for human kidneys 35 ; thus, that method is feasible for kidney applications as well. However, real-time elastography, virtual touch imaging, and virtual quantification are not available at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a small number of studies in which US strain and shear modulus-based elastography are used to evaluate the kidneys (9)(10)(11)(13)(14)(15)(16), and the majority of these studies have been performed in adults. There are several possible causes of altered renal stiffness, including parenchymal fibrosis (10,13,14) and hydronephrosis (11,12).…”
Section: Discussionmentioning
confidence: 99%